2012
DOI: 10.1186/1746-1596-7-116
|View full text |Cite
|
Sign up to set email alerts
|

Malignant transformation of Madelung’s disease in a patient with a coincidental diagnosis of breast cancer: a case report

Abstract: Madelung’s disease or multiple symmetric lipomatosis (MSL) is a rare disorder of unknown etiology which typically presents symmetrically subcutaneous accumulation of non-encapsulated adipose tissue which slowly grows around the neck, upper part of the arms, pelvis, back and thigh. This disease is also frequently associated with hepatopathy, glucose intolerance, hyperuricemia, and malignant tumors of the upper airways. Nevertheless, only one description of malignant transformation of Madelung’s disease has been… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 10 publications
0
24
0
2
Order By: Relevance
“…Surgery, such as liposuction, is another option—for removal of pre-existing lipid collections to relieve any compression symptoms. Although Enzi et al reported that MLD is associated with significant morbidity, MLD can rarely transform into liposarcoma, and there are only two documented cases in the literature 6 18 19. One salient point we would like to make in this case, was failure to get this ‘hidden diagnosis’ during previous hospital admissions, even though the patient had unique physical characteristics.…”
Section: Discussionmentioning
confidence: 87%
“…Surgery, such as liposuction, is another option—for removal of pre-existing lipid collections to relieve any compression symptoms. Although Enzi et al reported that MLD is associated with significant morbidity, MLD can rarely transform into liposarcoma, and there are only two documented cases in the literature 6 18 19. One salient point we would like to make in this case, was failure to get this ‘hidden diagnosis’ during previous hospital admissions, even though the patient had unique physical characteristics.…”
Section: Discussionmentioning
confidence: 87%
“…Routine chest radiographs may show abnormal symmetrical adipose mass accumulation. MRI is the best diagnostic tool in evaluation of the spread of adipose tissue, presence of tracheal compression, vascular topography within the fat mass, and exclusion of synchronous malignant disease [17]. However, overlap in a clinical appearance with other diseases can sometimes be misleading.…”
Section: Discussionmentioning
confidence: 99%
“…There are numerous previous case reports of concurrent cancer (Table III) (6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20) in WD/DD liposarcoma which add further evidence to support our observation; however, to our knowledge, the current study is the first to report data from a large case series and provide data from analysis of a national population-based cancer database to assess this occurrence. This study raises questions regarding the etiology of second primary cancer in patients with WD/DD liposarcoma.…”
Section: Discussionmentioning
confidence: 99%